Biomarker RIPK3 Is Silenced by Hypermethylation in Melanoma and Epigenetic Editing Reestablishes Its Tumor Suppressor Function - Arroyo Villora, Sarah; Castellanos Silva, Paula; Zenz, Tamara; Kwon, Ji Sun; Schlaudraff, Nico; Nitaj, Dafina; Meckbach, Cornelia; Dammann, Reinhard; Richter, Antje M.; Justus Liebig University Giessen (My University, 2024)
For several decades, cancers have demonstrably been one of the most frequent causes of death worldwide. In addition to genetic causes, cancer can also be caused by epigenetic gene modifications. Frequently, tumor suppressor genes are epigenetically inactivated due to hypermethylation of their CpG islands, actively contributing to tumorigenesis. Since CpG islands are usually localized near promoters, hypermethylation of the promoter can have a major impact on gene expression. In this study, the potential tumor suppressor gene Receptor Interacting Serine/Threonine Protein Kinase 3 (RIPK3) was examined for an epigenetic regulation and its gene inactivation in melanomas. A hypermethylation of the RIPK3 CpG island was detected by bisulfite pyrosequencing and was accompanied by a correlated loss of its expression. In addition, an increasing RIPK3 methylation rate was observed with increasing tumor stage of melanomas. For further epigenetic characterization of RIPK3, epigenetic modulation was performed using a modified CRISPR/dCas9 (CRISPRa activation) system targeting its DNA hypermethylation. We observed a reduced fitness of melanoma cells by (re-)expression and demethylation of the RIPK3 gene using the epigenetic editing-based method. The tumor suppressive function of RIPK3 was evident by phenotypic determination using fluorescence microscopy, flow cytometry and wound healing assay. Our data highlight the function of RIPK3 as an epigenetically regulated tumor suppressor in melanoma, allowing it to be classified as a biomarker.
Keywords: RIPK3; DNA (hyper)methylation; skin cutaneous melanoma; epigenetic editing; CRISPR-Cas9; deactivated dCas9; tumor suppressor gene; biomarker; cancer; ddc:570